MySQL cookbook - DuBois, Paul 1956- (O'Reilly, 2006)
Along with MySQL's popularity has come a flood of questions about solving specific problems, and that's where this Cookbook is essential. Designed as a handy resource when you need quick solutions or techniques, the book offers dozens of short, focused pieces of code and hundreds of worked-out examples for programmers of all levels who don't have the time (or expertise) to solve MySQL problems from scratch. The new edition covers MySQL 5.0 and its powerful new features, as well as the older but still widespread MySQL 4.1. One major emphasis of this book is how to use SQL to formulate queries.
Includes bibliographical references and index. - Print version record
Keywords: MySQL (Electronic resource); SQL (Computer program language); Database management; Relational databases; SQL (Langage de programmation); Bases de données; Gestion; Bases de données relationnelles; COMPUTERS; Programming Languages; SQL; Engineering & Applied Sciences; Computer Science